THE PREVALENCE OF UPPER LIMB PAIN AMONG VEENA PLAYERS: A CROSS-SECTIONAL SURVEY - Arumugam, Haari Haran; Balaraman, Thirumalaya; Bains, Balwant Singh; Sadeghi, Hassan (Revista Pesquisa em Fisioterapia, 2017)
Background: Instrumental musicians are a special risk group for repetitive motion injuries. Sizable percentages of them develop physical upper limb problems related to playing their instruments. Objective: The objective of this study was to investigate the prevalence of Upper Limb pain among Veena players. Method: This study was a descriptive cross sectional survey and fifty Veena Players participated in this study from a Music Academy. Trained Veena players aged between 12-50 and players who practice at least 3 times a week were included in the study. The period of pain, types of pain and location of pain were investigated by a self-developed questionnaire. In addition, Visual Analogue Scale (VAS) was also used to record the intensity of pain. Results: Descriptive analysis was used to analysis the data. The results showed that most of player had pain on shoulder; in addition, according to Visual Analogue Scale (VAS) most of participants have dull aching pain and shooting pain. Conclusion: In conclusion, this study's results also show that there is a low prevalence of Upper Limb pain among Veena players. Multiple evidences show that Upper Limb pain is indeed prevalent predominantly among musicians of Western music. In most of the time the pain type is of dull aching and/or shooting pain.